Keputusan Nasabah Menggunakan Produk Pembiayaan Mitra Emas iB Maslahah: Antara Physical Evidence, Promise, dan Customer Centric - Ainulyaqin, MH; Rakhmat, AS; Achmad, Listian I.; Fahamsyah, MH (Jurnal Ilmiah Ekonomi Islam, 2024)
This research will focus more on the Three Indicators in the Sharia Marketing Mix Strategy (Physical Evidence, Promise, and Customer Centric). It aims to determine and analyze the influence of the physical evidence, promise, and customer centric on customer decisions to use the gold partner financing product ib maslahah at Bank BJB Syariah KCP Lippo Cikarang. The sample used is all customers of Bank BJB Syariah Kcp Lippo Cikarang who are actively using the ib maslahah gold partner financing product, the sampling is by spreading a questionnaire link to all active customers who use the ib maslahah gold partner financing. The analytical tool used is multiple linear regression analysis using the SPSS version 21. The results of the partial study show that the physical evidence variable has no negative and significant effect on customer decisions to use the financing product of Mitra Emas iB Maslahah. While the promise and customer centric variables have a positive and significant impact on customer decisions to use the financing product of the ib maslahah partner gold. Meanwhile, simultaneously, the physical evidence, promise, and customer centric variables have a positive and significant impact on customer decisions to use the ib maslahah gold partner financing product.